Instilling Friendly Character Through Greeting Activities: The Pedagogical Role of Islamic Education Teachers in Public Junior High Schools - Septia Fahiroh; Syarnubi Syarnubi; Achmad Fadil; Nasrin, Ms. Samima; Firmansyah Firmansyah (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
This study aims to analyze the pedagogical role of Islamic Education (PAI) teachers in instilling friendly character through greeting activities at SMP Negeri 10 Palembang, amid increasing bullying, declining empathy, and weakening face-to-face interactions among students in the digital era. Using a qualitative method with a sociological approach, data were collected through in-depth interviews, participatory observation of the “Morning Greeting” activity and greeting practices in the classroom, as well as visual documentation and school documents. Informants were determined through purposive and snowball sampling until data saturation was reached, and analyzed using the Miles and Huberman model with triangulation verification of sources, methods, and time. The results of the study show that greeting activities function as social rituals that build positive interactions and strengthen emotional closeness among students. PAI teachers play a role through exemplifying the correct greeting, integrating the value of greeting into learning, habituating greetings before and after lessons, and reinforcing behavior through rewards. Consistent practice of greeting fosters empathy, social awareness, inclusive attitudes, and students' ability to cooperate and show solidarity. Additionally, greeting activities effectively reduce dependence on gadgets and restore the quality of face-to-face interactions, making them an important strategy for overcoming adolescent individualism in the digital age. This study confirms that greetings are a simple yet significant pedagogical intervention in shaping friendly character and creating a harmonious and inclusive school culture.